A REAPPRAISAL OF PALMOXYLON (ARECACEAE) SPECIES FROM THE UPPERMOST CRETACEOUS ALLEN FORMATION, RÍO NEGRO PROVINCE, ARGENTINIAN PATAGONIA (Ameghiniana, 2026)
Three species of Palmoxylon namely P. santarosense, P. rionegrense and P. valchetense, were described by Ancibor in 1995 for theuppermost Cretaceous (Campanian to Maastrichtian) Allen Formation at the Bajo de Santa Rosa locality, in northern Patagonia, Argentina. A revision of the original specimens, as well as previously unpublished remains, is carried out in light of modern descriptive procedures for palm stems. The diagnoses of the three species are emended to include new characters, as well as modifications on states of characters originally described. Epitypes for P. santarosense and P. valchetense are defined, to include more complete stems that allow a better characterization of these taxa. P. rionegrense is found referable to the subfamily Coryphoideae, with probable affinities to the tribe Caryoteae, while P. valchetense is referred to the tribe Trachycarpeae. P. santarosense is not referred to any subfamilial category due to inconclusive affinities. Affinities of these taxa provide wide climatic inferences, as they support tropical and non-tropical climates. The presence of Trachycarpeae in the latest Cretaceous of Patagonia challenges postulated divergence time estimations and biogeographic routes for this tribe.